Pengaruh fasilitas promosi dan daya tarik terhadap keputusan berkunjung pada wisata taman panda bima - Muhammad Fauji; Ita Purnama; Irma Mardian (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
The research objectives are to find out and analyze the influence of facilities on the decision to visit Panda Bima park tourism, to find out and analyze the influence of promotions on the decision to visit Panda Bima park tourism, to find out and analyze the influence of attractiveness on the decision to visit Panda Bima park tourism, to find out and analyze the influence of facilities, promotions and attractions on the decision to visit Panda Bima park tourism. This research is associative research, the instrument in this research uses a questionnaire with a Likert scale, data analysis techniques use the SPSS application. Based on the research results, it can be concluded that facilities do not have a significant influence on the decision to visit Panda Park tourism, promotion has a significant influence on the decision to visit Panda Park tourism, attractiveness has a significant influence on the decision to visit Panda Park tourism. Facilities, promotions and attractions have a significant influence on the decision to visit Panda Park tourism